2016
DOI: 10.21037/jgo.2016.06.16
|View full text |Cite
|
Sign up to set email alerts
|

Continuation of trastuzumab beyond disease progression in HER2-positive metastatic gastric cancer: the MD Anderson experience

Abstract: Background: Despite the wide spread use of trastuzumab in human epidermal growth factor receptor 2 (HER2) overexpressing metastatic gastric cancer patients, its optimal duration of administration beyond first-line disease progression is unknown. In HER2 overexpressing metastatic breast cancer, trastuzumab continuation beyond first-line disease progression has shown improvement in time to progression (TTP)without an increased risk of treatment related toxicity.Methods: HER2-overexpressing metastatic gastric can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…Al-Shamsi et al suggested that the continuation of trastuzumab beyond disease progression in patients with HER2-positive metastatic gastric cancer was feasible and safe in their retrospective analysis. 4 These findings coincided with the absence of cardiac events and other major adverse events (AEs) in our study population.…”
Section: Discussionsupporting
confidence: 86%
“…Al-Shamsi et al suggested that the continuation of trastuzumab beyond disease progression in patients with HER2-positive metastatic gastric cancer was feasible and safe in their retrospective analysis. 4 These findings coincided with the absence of cardiac events and other major adverse events (AEs) in our study population.…”
Section: Discussionsupporting
confidence: 86%
“…Based on the results of phase 3 ToGA study, trastuzumab combined with chemotherapy has become the standard treatment option for human epidermal growth factor receptor-2 (HER2) positive metastatic gastric cancer ( Bang et al, 2010 ). However, the positive rate of HER-2 in Chinese patients is only 12–13%, and simultaneously the value of continuous use of trastuzumab beyond progression (TBP) as second-line therapy is still controversial ( Al-Shamsi et al, 2016 ; Ter Veer et al, 2018 ). Until now, the approved anti-angiogenic drugs for metastatic gastric cancer include ramucirumab and apatinib.…”
Section: Discussionmentioning
confidence: 99%
“… 26 , 27 Platinum and taxanes were used in 18% and 14% of cases, respectively, as in the Russian cohort (19% and 14%), and more often than in the South Korean cohort (13% and 8%). 26 , 27 Trastuzumab was continued as the second line in 28.6% of patients who had it in the first line, even though this was outside the marketing authorization: a randomised phase‐2 study showed the lack of benefit of continuing trastuzumab in the second line after failure of a first line combining 5FU, platinum and trastuzumab, 25 while retrospective series suggest that maintaining HER2 blockade is feasible 32 , 33 and would lead to increased survival.…”
Section: Discussionmentioning
confidence: 99%